Psychological impact of multigene cancer panel testing in patients with a clinical suspicion of hereditary cancer across Spain. Issue 6 (26th March 2018) - Esteban, I.; Vilaró, M.; Adrover, E.; Angulo, A.; Carrasco, E.; Gadea, N.; Sánchez, A.; Ocaña, T.; Llort, G.; Jover, R.; Cubiella, J.; Servitja, S.; et al.
Abstract: Objective: Patients' psychological reactions to multigene cancer panel testing might differ compared with the single‐gene testing reactions because of the complexity and uncertainty associated with the different possible results. Understanding patients' preferences and psychological impact of multigene panel testing is important to adapt the genetic counselling model. Methods: One hundred eighty‐seven unrelated patients with clinical suspicion of hereditary cancer undergoing a 25‐gene panel test completed questionnaires after pretest genetic counselling and at 1 week, 3 months, and 12 months after results to elicit their preferences regarding results disclosure and to measure their cancer worry and testing‐specific distress and uncertainty. Results: A pathogenic variant was identified in 38 patients (34 high penetrance and 4 moderate penetrance variants), and 54 patients had at least one variant of uncertain significance. Overall, cancer panel testing was not associated with an increase in cancer worry after results disclosure ( P value = .87). Twelve months after results, carriers of a moderate penetrance variant had higher distress and uncertainty scores compared with carriers of high penetrance variants. Cancer worry prior to genetic testing predicted genetic testing specific distress after results, especially at long term ( P value <.001). Most of the patients reported the wish to know all genetic results. Conclusions: Our results suggest that patients can psychologically cope with cancer panel testing, but distress and uncertainty observed in carriers of moderate penetrance cancer variants in this cohort warrant further research.